Analysis of the Influence of Consumer Behavior, Influencer Marketing, and Product Packaging on Purchasing Decisions for Reyshaka Interior Products - Nike Nanda Pratiwi; Imam Syairozi; Evi Fitrotun (Sean Institute, 2025)
Study This aim For know analysis influence of Influencer marketing and product packaging to decision purchase product Reyshaka Interior. Type of research used is study quantitative descriptive . Population in study This is 270 people with amount a sample of 100 consumers was taken from long-time customer of Reyshaka Interior. Data collection techniques deploy questionnaire to respondents . Analysis of the data used is PLS SEM. Study This starting in November 2023 to March 2024. From the results study can concluded that variable influencer marketing and product packaging in a way damn influential significant on purchasing decisions product Reyshaka Interior with value 0.000. The most dominant is variable influencer marketing against behavior consumer with value 0.395. Variable behavior consumers can do it too mediate variable influencer marketing and product packaging in a way damn influential significant on purchasing decisions product Reyshaka Interior with values 0.031 and 0.042.